The Influence of Online Reviews and Price Perception on Rocket Chicken Consumers' Purchase Decision, with the Perception of Halalan Thayyiban as a Mediating Variable - Mila Zahrotun; Yeny Fitriyani; Ahmad Muhibin (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of online reviews and price perception on purchasing decisions, with the perception of Halalan Thayyiban as a mediating variable, among Rocket Chicken consumers. The study employs a quantitative approach with a causal (cause-and-effect) design. The study sample consisted of 150 respondents selected using purposive sampling. Data were collected through a questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results indicate that online reviews and price perception have a positive and significant effect on Purchase Decision and Perception of Halalan Thayyiban. This suggests that halal status and product quality may be viewed as basic prerequisites (hygiene factors) by consumers. Furthermore, Perception of Halalan Thayyiban do not mediate the effects of online reviews or price perception on Purchase Decision. These findings suggest that Purchase Decision are more directly influenced by online reviews and price perception, rather than through perceptions of Halalan Thayyiban. This study implies that businesses need to focus on managing customer reviews and setting appropriate prices to enhance consumer Purchase Decision.